Reseña/Review (Illouz, Eva "¿Por qué duele el amor?", Madrid: Clave Intelectual/Kazt, ISBN: 9788492946471, 364 págs., 2012) - Subirats, Marina (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2013)
Reseña/Review (Illouz, Eva "¿Por qué duele el amor?", Madrid: Clave Intelectual/Kazt, ISBN: 9788492946471, 364 págs., 2012)